The Effect of Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Current Ratio (CR) on Return on Assets (ROA) in Property Companies Listed on the Indonesia Stock Exchange in 2022-2023 - Utami, Ayu Putri; Andriani, Nini; Lestari, Tri Ayu; Fitrisam, Syarifah Aliyah; Iskandar, Rizkiani; Luneto, Abdul Razik (XXXX-XXXX, 2024)
This study aims to determine the effect of Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Current Ratio (CR) on Return on Assets (ROA) in Property Companies Listed on the Indonesia Stock Exchange in 2022-2023. This study uses a quantitative approach with secondary data obtained from the company's annual report. The population in this study were all property companies listed on the IDX. Data analysis was performed using multiple linear regression. The results of this study indicate that DER has a significant negative effect on ROA, DAR has a significant positive effect on ROA, the CR variable has no significant effect on ROA.